“More beautiful and more terrible than anything anyone has ever said”: 9/11, BLM, and the creation of an American identity - Batt, Joanna; Joseph, Michael L.; Brown, Anthony L. (Critical Education, 2025)
We contend that September 11th and the Black Lives Matter movement acted as critical moments that challenged earlier notions of the American identity and the false pretenses of a racially, religiously, and culturally equitable United States. Using theoretical lenses of double consciousness and cultural memory, we further that the way newspapers present narratives of these events emphasizes how the memories of a country and who they think they are fluctuate and change throughout time. We end with implications for social studies spaces that seek to explore 9/11 and the Black Lives Matter movement’s impact on American national identity, and/or hope to critique how memories shaped by media outlets like newspapers reinscribe or counter previous notions of the American national identity.